Maritime Economic Transformation through Marine Engineering Innovation - Aerin Regina Putri; Putri Adelia (Journal of Economic Growth and Development Review, 2026)
Maritime economic transformation is one of the important strategies in encouraging sustainable economic growth, especially for archipelagic countries with large potential for marine resources. Innovation in the field of marine engineering plays a significant role in increasing efficiency, productivity, and added value in the maritime sector. This article discusses the role of marine engineering innovation in driving maritime economic transformation through the development of coastal and offshore infrastructure, the use of modern marine technology, and the improvement of the quality of human resources. The discussion shows that the integration of marine engineering innovation with maritime economic policies is able to strengthen competitiveness, create entrepreneurial opportunities, and support sustainable blue economy development.